Common Diagnoses and Outcomes in Elderly Patients Who Present to the Emergency Department with Non-Specific Complaints. Issue 5 (15th June 2015) - Quinn, Kathleen; Herman, Michael; Lin, Daren; Supapol, Wendy; Worster, Andrew
Abstract: Objective: Elderly patients often present to the emergency department (ED) with non-specific complaints. Previous studies indicate that such patients are at greater risk for life-threatening illnesses than similarly aged patients with specific complaints. We evaluated the diagnoses and outcomes of elderly patients presenting with non-specific complaints. Methods: Two trained data abstractors independently reviewed all records of patients over 70 years old presenting (to two academic EDs) with non-specific complaints, as defined by the Canadian Emergency Department Information System (CEDIS). Outcomes of interest were ED discharge diagnosis, hospital admission, length of stay, and ED revisit within 30 days. Results: Of the 743 patients screened for the study, 265 were excluded because they had dizziness, vertigo, or a specific complaint recorded in the triage notes. 419 patients (87.7%) presented with weakness and 59 patients (12.3%) presented with general fatigue or unwellness. The most common diagnoses were urinary tract infection (UTI) (11.3%), transient ischemic attack (TIA) (10.0%), and dehydration (5.6%). There were 11 hospital admissions with median length of stay of five days. Eighty-one (16.9%) patients revisited the ED within 30 days of discharge. Regression analysis indicated that arrival to the ED by ambulance was independently associated with hospital admission. Conclusions: Our results suggest that elderly patients presenting to the ED with non-specific complaints are not at high risk for life-threatening illnesses. The most common diagnoses are UTI, TIA, and dehydration. Most patients can be discharged safely, although a relatively high proportion revisit the ED within 30 days. Résumé: Objectif: Il est fréquent que des personnes âgées consultent au service des urgences (SU) pour des symptômes généraux. D'après des études antérieures, ces patients connaissent un risque plus grand de maladies potentiellement mortelles que les patients de même âge ayant des symptômes précis. Aussi les auteurs ont-ils évalué les diagnostics posés chez des personnes âgées examinées pour des symptômes généraux, de même que l'issue. Méthode: Deux personnes formées à l'abstraction de données ont examiné, chacune de leur côté, tous les dossiers de patients âgés de plus de 70 ans, qui ont consulté dans deux SU d'hôpitaux universitaires pour des symptômes généraux tels qu'ils sont définis dans le Canadian Emergency Department Information System (CEDIS). Les principaux critères d'évaluation comprenaient le diagnostic au moment du congé du SU, l'hospitalisation, la durée de séjour et les nouvelles consultations au SU dans les 30 jours suivants. Résultats: Sur 743 patients présélectionnés pour l'étude, 265 ont été écartés parce qu'on faisait déjà mention d'« étourdissements » ou de « vertiges » ou encore de symptômes précis dans les notes relatives au triage. Sur le nombre restant de patients, 419 (87, 7 %) présentaient de la faiblesse, et 59 (12, 3 %), de la fatigue générale ou un état de malaise. Les diagnostics les plus fréquents étaient une infection des voies urinaires (IVU) (UTI) (11, 3 %), un accident ischémique transitoire (AIT) (10, 0 %) et la déshydratation (5, 6 %). Il y a eu 11 hospitalisations, et la durée médiane de séjour était de 5 jours. Quatre-vingt-un patients (16, 9 %) ont consulté de nouveau au SU dans les 30 jours suivant le congé. Une analyse de régression a révélé que l'arrivée en ambulance au SU était en relation indépendante avec l'hospitalisation. Conclusions: D'après les résultats de l'étude, les personnes âgées qui consultent au SU pour des symptômes généraux ne connaîtraient pas un risque élevé de maladies potentiellement mortelles. Les diagnostics les plus fréquents sont les IVU, les AIT et la déshydratation. La plupart des patients peuvent obtenir leur congé du service en toute sécurité, et ce, malgré le fait qu'une proportion relativement élevée consulte de nouveau au SU dans les 30 jours suivants.